A history and historiography of foreign languages teaching and learning in Portugal*. Issue 1 (1st January 2018) - Santos, Ana Clara
ABSTRACT: This 'state of the art' review on the history of language teaching in Portugal provides an opportunity for a historiographical analysis, highlighting the relationships between languages, the links between languages and educational policy and implementation, and the cultural implications resulting from this. Researching language teaching and learning inevitably involves exploring a particular world view from a historiographical and ideological point of view. From this perspective, we focus in this article on the notion of 'disciplinarisation' in order to develop a picture of foreign language teaching/learning in Portugal during the nineteenth century, the period that has been most studied by the Portuguese Association for the Teaching of the History of Foreign Languages and Literatures (APHELLE). This period saw the setting up of the state school system, successive reforms of state education, and growth in the production of pedagogic materials, all of which reflect the hierarchisation of knowledge based on a particular view of education and the world.